UPAYA KEPOLISIAN DALAM MENANGGULANGI PENYELUNDUPAN BAWANG MERAH DI WILAYAH HUKUM POLRES SIAK - Zulkarnain S.; Suci Yunita (JOURNAL EQUITABLE, 2023)
"Criminal acts of smuggling are criminal acts related to the release of goods or money from Indonesia abroad (export) or the entry of goods or money from abroad to Indonesia (import)". Smuggling is the act of carrying goods or people illegally and in secret without complying with the applicable laws and regulations. The smuggling of shallots that occurred in the Siak district area is very disturbing to the community, especially shallot farmers because it will affect their opinions and harm the state's finances, therefore it is necessary to find solutions and appropriate steps to overcome them, so as to increase domestic competitiveness and boost State revenue from import duties and taxes Keywords: smuggling, countermeasures, shallots